2020
DOI: 10.1017/s1041610220000332
|View full text |Cite
|
Sign up to set email alerts
|

The quality of the relationship perceived by spouses of people with young-onset dementia

Abstract: Background: Young-onset dementia (YOD) has a profound impact on spouses. However, little is known on how the quality of the relationship changes over time in YOD. This study aims to determine how the quality of the relationship changes over time and identify predictors of this change. Methods: This study used data from the NEEDs in Young onset Dementia (NeedYD) study. The primary outcome measure was the quality of the relationship perceived by spouses measured throughout 24 months. Basel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 44 publications
2
11
0
Order By: Relevance
“…The decreasing carer RQ scores and the stable scores of person with dementia are in line with other studies (Bruinsma et al, 2020;Clare et al, 2012;Spector et al, 2016). Although family carers may try to maintain their previous RQ (Wadham et al, 2016), the caring process can be overwhelming and this may lead to the observed reduction in RQ (Egilstrod et al, 2019;Evans & Lee, 2014).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The decreasing carer RQ scores and the stable scores of person with dementia are in line with other studies (Bruinsma et al, 2020;Clare et al, 2012;Spector et al, 2016). Although family carers may try to maintain their previous RQ (Wadham et al, 2016), the caring process can be overwhelming and this may lead to the observed reduction in RQ (Egilstrod et al, 2019;Evans & Lee, 2014).…”
Section: Discussionsupporting
confidence: 86%
“…This is in line with previous evidence that informal support mechanisms may reduce the burden of caregiving (Del-Pino-Casado et al, 2018) and impact positively on RQ. A study with carers of people with young-onset dementia (Bruinsma et al, 2020) showed an association between 'seeking social support' and lower RQ. The authors suggested this might be due to reverse causality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The early onset of dementia can exacerbate these aspects due to the premature impairment of family and social roles. Previous research showed that spouses of people with early onset AD (EOAD) precociously experienced negative changes due to responsibility shifting and social isolation [11]. Pressed by the dual care demand for both children and relatives, the members of the "sandwich generation" caregivers (i.e., the emerging cohort of caregivers, mainly represented by middle-aged women, who were caring for maturing children and aging relatives simultaneously) [12] frequently showed high level of burden, stress, and mood disorders, with family distress and higher risk of institutionalization [13], especially when behavioral-psychological symptoms occurred [14].…”
Section: Introductionmentioning
confidence: 99%